Ligand binding and signalling pathways of PTH receptors in sea bream (Sparus auratus) enterocytes - Rotllant, J. (2014)
Whole animal studies have indicated that Ca2+ uptake by the gastrointestinal tract is regulated by the action of parathyroid hormone-related peptide (PTHrP) in teleost fish. We have characterised PTH receptors (PTHR) in piscine enterocytes and established, by using aminoterminal PTHrP peptides, the amino acid residues important for receptor activation and for stabilising the ligand/receptor complex. Ligand binding of 125I-(1–35tyr) PTHrP to the membrane fraction of isolated sea bream enterocytes revealed the existence of a single saturable high-affinity receptor (KD=2.59 nM; Bmax=71 fmol/mg protein). Reverse transcription/polymerase chain reaction with specific primers for sea bream PTH1R and PTH3R confirmed the mRNA expression of only the later receptor. Fugu (1–34) PTHrP increased cAMP levels in enterocytes but had no effect on total inositol phosphate accumulation. The aminoterminal peptides (2–34)PTHrP, (3–34)PTHrP and (7–34) PTHrP bound efficiently to the receptor but were severely defective in stimulating cAMP in enterocyte cells indicating that the first six residues of piscine (1–34)PTHrP, although not important for receptor binding, are essential for activation of the adenylate cyclase/phosphokinase A (AC-PKA)-receptor-coupled intracellular signalling pathway. Therefore, PTHrP in teleosts acts on the gastrointestinal tract through PTH3R and the AC-PKA intracellular signalling pathway and might regulate Ca2+ uptake at this site. Ligand-receptor binding and activity throughout the vertebrates appears to be allocated to the same amino acid residues of the amino-terminal domain of the PTHrP molecule.